Lattice-based lightweight cryptosystem. (22nd August 2022) - Jain, Shivani; Padmavathy, R.
The lattice-based cryptographic constructions are emerging as a major contender of post quantum cryptography. The power-of-2 cyclotomic rings are widely used in lattice-based solutions but these rings have limitations in choice and are scarce. In the proposed work, prime cyclotomic rings are considered for investigation as they enjoy the same security and benefits as power-of-2 rings. In today's world of resource constraint devices, cryptographic constructions are expected to be simpler and lightweight, compared to conventional cryptography. The major concern in the deployment of lattice-based constructions is the size of the payloads. The byte modulus, which is an adaption of the LAC scheme, is used to overcome this problem. Our results show that the proposed scheme is more compact but reasonably secure and relatively efficient in comparison to other popular solutions such as LAC. Further, to withstand decryption failure, the popular BCH and Turbo code are used as error correction with the proposed scheme. The performance of BCH and Turbo code along with prime cyclotomic rings with or without byte modulus is studied and reported.